PREPARATION AND PROPERTIES OF PURIFIED RICKETTSIAL SUSPENSIONS - RUIZ CASTANEDA, CARMEN (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1976)
Four applications of 6 lb of DDT per 100 gal of water significantly reduced populations of the Mexican fruit fly, Anastrepha ludens, in mango trees in Cuernavaca, Morelos, Mexico 20% DDT dust was much less effective Four applications of 6 lbs benzene
J IMMUNOL VIRUS RES EXP CHEMOTHER
Keywords: PREPARATION, PROPERTIES, PURIFIED, RICKETTSIAL, SUSPENSIONS; CIENCIAS MEDICAS; CIENCIAS CLINICAS; GINECOLOGIA